E-Kawalselia Management Portal for Information Technology Faculty - Salehuddin, Shuib (2004)
This thesis describe about development of E-Kawalselia Management Portal. The application consists of three main modules that Digital Drop Box (E-mail application), Forum and Information. The purpose of the application is to solve Unit Kawal Selia (UKS) communication problems. The Digital Drop Box is used t submit message or file through the network within members. All members can use Forum module to discuss about certain topic. For the Information module it provide latest information about courses, coordinators, and past examination question. The UML based Web Engineering (UWE) methodology was use for the development of this application. Lastly, the thesis also elaborate about an advantage and suggestion to improve the efficiency of the application.